Contemporary issues in geoenvironmental engineering : Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Infrastructures /: Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Infrastructures. (2018) - Unknown
No abstract available